2020
DOI: 10.29303/jpft.v6i1.1683
|View full text |Cite
|
Sign up to set email alerts
|

Profil Miskonsepsi Mahasiswa Calon Guru Fisika Ditinjau Dari Berbagai Representasi Pada Materi Gerak Lurus Dan Gerak Parabola

Abstract: Misconceptions are one of the problems that often occur in education. This objected aims to identify misconceptions of pre-service physics teachers' in motion concept from various representations. The method used in this research is descriptive method. A total of 40 pre-service physics teachers' at a university in the city of Mataram were involved in this study. The instrument used in the study was a three tier test with open reasons. The reasons have been made to be open aims so that pre-service physics teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…The causes of students' misconceptions are the ability to receive lessons in multi-representation from the students themselves, which is still lacking, causing students to experience misconceptions, from the way the teacher teaches material that has not yet been multirepresentation involving mathematical representations, pictures, graphics and verbal, so that students do not understand the material well and experience it misconceptions, the level of student confidence from the answers that students have chosen can also lead to misconceptions (Nurulwati, 2014, Mursadam, 2017, Busyairi, 2020, Lestari, 2015. Based on table 5 above, it can be seen that the average level of students' misconceptions of class X Natural Sciences in PSHS Balung on the material of momentum and impulses through the mathematical representation approach is 32.78%.…”
Section: Resultsmentioning
confidence: 99%
“…The causes of students' misconceptions are the ability to receive lessons in multi-representation from the students themselves, which is still lacking, causing students to experience misconceptions, from the way the teacher teaches material that has not yet been multirepresentation involving mathematical representations, pictures, graphics and verbal, so that students do not understand the material well and experience it misconceptions, the level of student confidence from the answers that students have chosen can also lead to misconceptions (Nurulwati, 2014, Mursadam, 2017, Busyairi, 2020, Lestari, 2015. Based on table 5 above, it can be seen that the average level of students' misconceptions of class X Natural Sciences in PSHS Balung on the material of momentum and impulses through the mathematical representation approach is 32.78%.…”
Section: Resultsmentioning
confidence: 99%
“…different horizontal veloticy [11] The distributional results of students' answer in the first challenge shown that majority of students (46.1%) still have understanding that the initial velocity will affect the time to achieve the ground. The students' selection of reason was dominantly discovered that they still grasp the incorrect perception that bigger velocity, farther the maximum range (56.6%).…”
Section: Fig 2 the First Items Of Figural Representation Two Wooden B...mentioning
confidence: 99%
“…Research shows that 66% of students demonstrate misconceptions in Newton's Law [6], 39.9% of students possess misconceptions on dynamic electricity [7], 26.2% of students experience misconceptions on light [8], 51.27% of students experience misconceptions on temperature and heat [9], and 80.11% of students experience misconceptions on linear motion [10]. Based on these documentations, it can be captured that students still experience misconceptions in almost entire physics topics [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toedtanya & Wuttiprom [9] covered energy concept as well as Safriana & Nuraini [10] found misconception on mechanics concept about guideline framework centered on self, heavy object fell faster than light object, object mass could make object stop moving, object movement was force representation on objects and force source on object was a result of hits. Other research were Riggs [11] about black hole, Syuhendri [12] about gravitation, Dessytya, et al [13] for gravitation force concepts, light pace, frequency and amplitude, static electric force, and visible objects [13] and Busyairi & Muhammad [14] who indicated students' misconception on linear, vertical, and parabolic movement concept. Suma, et al [15] discovered students' misconception on electricity material whereas Tumanggor, et al [16] found misconception on wave frequency, sound wave, and medium objects.…”
Section: Introductionmentioning
confidence: 99%